The Song of Songs in European Poetry (Twelfth to Seventeenth Centuries) - Caporicci, Camilla (Brepols, 2024)
Traditionally attributed to King Solomon and defined by Rabbi Aqiva as the Holy of Holies among the sacred Scriptures, the Song of Songs is one of the most fascinating and controversial biblical books. Celebrated as a key to the supreme mystery of the union between God and the faithful, this ambivalent book, which combined a sensual celebration of love with a well-established tradition of allegorical interpretation, was a text crucial to both the Middle Ages and the Renaissance, and held a particular appeal for poets. Indeed, the Song of Songs played a significant role in the development of European poetry from its very beginning, creating an exceptional convergence of sacred and secular languages and horizons of meaning. Written by a group of distinguished international scholars, this volume explores the complex and multifaceted processes through which the Song of Songs entered, influenced, and interacted with medieval and Renaissance European poetry (twelfth to seventeenth centuries). Focusing on both individual authors – including Peter Riga, Dante Alighieri, Richard Rolle, and George Herbert – and particularly relevant poetic traditions – including Hebrew liturgical poetry and the Tristan and Ysolt tradition, Middle English and Petrarchan lyric, Renaissance verse versions and seventeenth-century musical compositions, dissident and prophetic texts – the volume unveils the relevant role played by the biblical book in the development of European poetry, thought and spirituality, highlighting its ability to contribute to different poetic genres and give voice to a variety of religious, political, philosophical, and artistic intentions.